Combined Physiological and Transcriptomic Analysis Reveals Key Regulatory Networks and Potential Hub Genes Controlling Chilling Tolerance During Soybean Germination - Jianguo Xie; Yuhong Zheng; Guang Li; Wei Zhang; Fanfan Meng; Xuhong Fan; Xingmiao Sun; Yunfeng Zhang; Mingliang Wang; Qingshan Chen; Shuming Wang; Hongwei Jiang (Plant Direct)
ABSTRACT Chilling is an important limiting factor for seed germination of soybean (Glycine max [L.] Merr.). To reveal the regulatory mechanism of chilling tolerance during the soybean germination stage, based on previous studies, the chilling tolerance line R48 and chilling sensitive line R89 in chromosome segment substitution lines were selected for physiological index determination and transcriptome sequencing. It was found that reactive oxygen species (ROS) scavenging system related enzymes, ROS, and osmotic regulators were significantly different between the two lines. Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes enrichment were performed on the differentially expressed genes obtained by transcriptome sequencing. It was found that terms or pathways related to flavonoids, unsaturated fatty acids, and abscisic acid were highly enriched. In addition, weighted gene coexpression network analysis (WGCNA) method was used to analyze the physiological index data and transcriptome sequencing data. Four main coexpression modules significantly related to physiological indicators were obtained, and the hub genes in each module were screened according to eigengene‐based connectivity value. Haplotype analysis of important candidate genes using soybean germplasm resources showed that there were significant differences in germination indexes between different major haplotypes of Glyma.17G163200. Based on the results of enrichment analysis and WGCNA, the regulation model of low temperature tolerance during soybean germination was preliminarily drawn. This study will provide theoretical guidance for analyzing the molecular regulation mechanism of cold tolerance in soybean germination stage.